Exploring the prevalence and risk factors of diabetic retinopathy in early onset type 2 diabetes mellitus: a study in Kuantan, Pahang - Shamsudin, Nurzawani; Md Aris, Mohd Aznan; Salam, Adzura; Mohd Rus, Razman (Academy of Family Physicians of Malaysia, 2024)
Introduction: The global prevalence of early-onset type 2 diabetes in adults has increased worldwide. Thus, it contributes large impact on the development of macrovascular and microvascular complications. Diabetic retinopathy is the major cause of adult blindness in developed countries. The main aim of this study is to ascertain the prevalence of diabetic retinopathy and its associated risk factor in patients with early onset type 2 diabetes mellitus patients attending primary care in Kuantan. Methods: A cross-sectional study was conducted at 4 selected government health clinics in Kuantan, Pahang. A total of 180 early onset type 2 diabetes patients were randomly selected. Early onset type 2 diabetes mellitus was defined as patient diagnosed with type 2 DM before the age of 40 years old. Latest fundus was taken using digital retinal imaging technology. Data were collected on demographic, clinical parameter, cardiovascular risk factor with micro and macrovascular complication. Results: The prevalence of diabetic retinopathy in early onset type 2 DM is 70.7% with 29.8% of it were mild NPDR, 27.6% were moderate NPDR, 8.8% were severe NPDR and 4.4% were PDR. 8.8% also had diabetic maculopathy. The duration of DM, HbA1c level and diabetic kidney disease were significantly associated with diabetic retinopathy in our study. Conclusion: More than half of the people with early onset diabetes have diabetic retinopathy within 10 years of diabetes duration. Good glycaemic control along with regular eye screening can prevents visual loss due to diabetic retinopathy in early onset of Type 2 diabetes patient.